Divertículo esofágico en un pastor alemán : reporte de caso (2007)
ABSTRACT: A German Shepard dog was attended presenting an infectious gastroenteritis. Once the dog responded to treatment, it was noticed that the patient regurgitated frequently. In the barium esophagogram it was detected a big esophageal dilatation in the proximal third of the thoracic esophagus, and the upper endoscopy confirmed an esophageal diverticulum. The surgical intervention included a lateral thoracotomy with esophageal diverticulum resection, thoracic tube drainage with a Heimlich valve, and a gastrostomy tube placement for enteral nutrition. The patient recovered satisfactory without any complication. Esophageal diverticulum is infrequent in dogs and its rupture can lead to critical conditions as mediastinitis and death. Surgical resection is essential in the treatment of esophageal diverticulum in cases were clinical symptoms are important.